Lasers in Endodontics- A Review of Literature - P.A.Vasishta1 , K Anjaneyalu2 , Vinay Sivaswamy3 , K Anjaneyalu4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Lasers are commonly used to reshape our gums during root canal procedures and to kill bacteria. Applicationof lasers in dentistry has been increased due to its safety and effectiveness in dental treatments. Lasers havebeen used as coadjuvant treatment in endodontic therapy with respect to both low-intensity laser therapy(LILT) and high-intensity laser treatment (HILT) to improve clinical procedures’ success rate. The majorprocedures done with lasers in endodontics are dentin hypersensitivity, removal of carious tissues, toothpreparations, pulp capping or pulpotomy and also in root canal treatment.Lasers are often used to removemouth lesions and to soothe discomfort. A thorough literature search was performed using the databaselike Pubmed, google scholar, BioRxiv, MESH database using the keywords ‘light amplification device’and ‘Endodontics’ and also their types with no date and year restrictions.12 articles with similar data havebeen found which were analysed and have been included in this study. Talulation were done using googledocuments. The recent articles discussed in this study help us in gaining further knowledge about lasers andtheir usage in endodontics. The various methods of using lasers discussed in this article has been widelyused by dental practitioners with 100% success rate. So it has been concluded that lasers are well establishedinstruments. Upcoming research based on lasers are showing more benefits and ability to perform lessinvasive procedures with greater comfort of patients has led to the development of lasers in modern dentistryespecially in endodontics.